Synthesis and analysis of a high‐performance low‐cost permanent magnet brushless DC motor - Petkovska, Lidija; Lefley, Paul; Cvetkovski, Goga (Emerald, 2012)
The paper presents design development of a novel high‐performance low‐cost 6/4 pole permanent magnet brushless DC (PMBLDC) motor. The objective is to show how the cogging torque of this new design is minimised by determining the optimum stator pole arc length and the best shoe thickness. At the beginning a step‐by‐step design synthesis of a reference 6/4 pole PMBLDC motor with concentrated 3‐phase windings and asymmetric stator pole arcs is presented. It is followed by a full performance analysis of the reference motor. The FEM for electromagnetic field computation is employed. The characteristics of the motor are calculated and analysed. By simple variation of the stator pole geometry, two‐stage design optimisation for cogging torque minimisation is performed, and an optimised motor model is proposed. The comparative analyses of the reference and optimised motor models show the advantages of the proposed novel design. The focus is to show the sensitivity of the cogging torque due to changes in the stator pole shoe design parameters, such as arc length and thickness, which are discretely changed inside the prescribed constraints, and the solution matrix is derived. It was found the optimised stator pole design, providing minimum cogging torque, has the original arc length 85° and pole shoe thickness 4 mm. Thus, the peak‐cogging torque from 0.294 Nm is reduced to respectable value 0.142 Nm. The paper presents an original approach to synthesis of 6/4 PMBLDC new structured motor. A two‐step design procedure is introduced and optimised stator geometry is defined, minimising the cogging torque and, at the same time, improving the profile of back electromotive force (EMF) of the motor.
Keywords: electric motors, torque, optimal design, permanent magnet motor, finite element analysis, cogging torque, back EMF